2005
DOI: 10.1590/s0102-86502005000700008
|View full text |Cite
|
Sign up to set email alerts
|

Catechol inhibits FADH2-linked respiration in rat liver mitochondrial fraction

Abstract: Catechol produced an inhibition of basal respiration associated to FADH2 in isolated liver mitochondria that could lead to cytotoxicity, ROS generation and cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Studies conducted by Barreto et al [2005] demonstrated that catechol inhibits liver mitochondrial state 2 FADH 2 -linked respiration. These data suggest the inhibition of mitochondrial respiration by catechol as a potential mechanism of its cytotoxicity.…”
Section: Catechol and Dna Damage: An Oxidative Pathwaymentioning
confidence: 99%
“…Studies conducted by Barreto et al [2005] demonstrated that catechol inhibits liver mitochondrial state 2 FADH 2 -linked respiration. These data suggest the inhibition of mitochondrial respiration by catechol as a potential mechanism of its cytotoxicity.…”
Section: Catechol and Dna Damage: An Oxidative Pathwaymentioning
confidence: 99%
“…The results also showed for the first time that 3MC significantly inhibited state 2 FADH 2 -linked respiration in rat brain nonsynaptic mitochondria. In a previous work, 1,2-dihydroxybenzene (catechol) also inhibited state 2 FADH 2 -linked respiration of rat liver mitochondria (Barreto et al, 2005). These data suggest that catechols may interfere with the respiratory chain.…”
Section: Discussionmentioning
confidence: 54%
“…9 Although the aim of this work was not to study the effects of catechol on mitochondrial respiration in GL-15 cells, a previous work showed that catechol inhibited state 2 FADH 2 -linked respiration of rat liver mitochondria. 25 Furthermore, 3-methylcatechol also inhibited state 2 FADH 2 -linked respiration in rat brain nonsynaptic mitochondria. 26 Cells can die by two major mechanisms: necrosis or apoptosis.…”
Section: Discussionmentioning
confidence: 94%